Climate Finance and its Role in Climate Policy - Scott, Claire (Journal of Climate Policy, 2023)
Purpose: The main objective of this study was to explore climate finance and its role in climate policy. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to climate finance and its role in climate policy. Preliminary empirical review revealed that the importance of continuously assessing and adapting climate finance mechanisms to meet evolving climate policy needs. Climate finance is not merely a financial resource but a crucial tool in the global fight against climate change, and its effective deployment can significantly contribute to achieving the goals set forth in international climate agreements like the Paris Agreement. Unique Contribution to Theory, Practice and Policy: The Neoliberal Institutionalism theory, Political Economy theory and the Environmental Governance theory may be used to anchor future studies on climate finance. The study suggested for enhanced transparency and accountability, strengthening capacity building, alignment of climate finance with national priorities, promoting innovative financing mechanisms and facilitating south-south cooperation.